Gender diversity and corporate sustainability performance: empirical evidence from India - Ritu Pareek; Tarak Nath Sahu; Arindam Gupta (Vilakshan (XIMB Journal of Management))
Purpose – This study aims to attempt to evaluate and establish the relationship between gender diversity (GD) on the board and corporate sustainability performance. Design/methodology/approach – A sample of 212 non-financial companies listed on the National Stock Exchange has been considered for a period of 2013–2014 to 2018–2019. For the purpose of the analysis, this study has conducted the static panel data model analysis and also some diagnostics tests to arrive at robust results. Findings – This study, from its analysis, interprets that GD or the proportion of women directors in the company plays a significant role in the decisions related to the sustainability performance of the company. Alongside GD, the profitability of the company, measured in terms of Tobin’s Q, and firm size are also seen to have a positive impact on the sustainability performance of the company. Practical implications – This study from its findings contributes to the existing works of literature by highlighting the impact of GD on the sustainability performance of the firm. This study thus recommends the recruitment of an ample number of females in the top-notch positions of the board to create a gender-diverse management team to reap the benefits of leadership styles of both genders. Originality/value – Very few studies have been conducted on the dynamics of women’s directorship, especially in an emerging economy like India. This study thus tries to fill this important gap in the literature by examining the relationship between board GD and sustainability performance of Indian firms.